Expression of dihydropyridine receptor (Ca2+ channel) and calsequestrin genes in the myocardium of patients with end-stage heart failure. - T Takahashi; P D Allen; R V Lacro; A R Marks; A R Dennis; F J Schoen; W Grossman; J D Marsh; S Izumo (The Journal of Clinical Investigation, 1992)
Cytoplasmic free calcium ions (Ca2+) play a central role in excitation-contraction coupling of cardiac muscle. Abnormal Ca2+ handling has been implicated in systolic and diastolic dysfunction in patients with end-stage heart failure. The current study tests the hypothesis that expression of genes encoding proteins regulating myocardial Ca2+ homeostasis is altered in human heart failure. We analyzed RNA isolated from the left ventricular (LV) myocardium of 30 cardiac transplant recipients with end-stage heart failure (HF) and five organ donors (normal control), using cDNA probes specific for the cardiac dihydropyridine (DHP) receptor (the alpha 1 subunit of the DHP-sensitive Ca2+ channel) and cardiac calsequestrin of sarcoplasmic reticulum (SR). In addition, abundance of DHP binding sites was assessed by ligand binding techniques (n = 6 each for the patients and normal controls). There was no difference in the level of cardiac calsequestrin mRNA between the HF patients and normal controls. In contrast, the level of mRNA encoding the DHP receptor was decreased by 47% (P less than 0.001) in the LV myocardium from the patients with HF compared to the normal controls. The number of DHP binding sites was decreased by 35-48%. As reported previously, expression of the SR Ca(2+)-ATPase mRNA was also diminished by 50% (P less than 0.001) in the HF group. These data suggest that expression of the genes encoding the cardiac DHP receptor and SR Ca(2+)-ATPase is reduced in the LV myocardium from patients with HF. Altered expression of these genes may be related to abnormal Ca2+ handling in the failing myocardium, contributing to LV systolic and diastolic dysfunction in patients with end-stage heart failure. Images